PENGARUH EARNING PER SHARE DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Siti Nuridah; Joelianti Dwi Supraptiningsih; Ade Irawan; Edwin Jonathan Panjaitan; Nuri Maharani (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
This study aims to discuss the effect of earnings per share (EPS) and dividend policy on firm value. Firm value is used as a measure of the success of a company. By increasing the value of the company can be interpreted as an increase in the prosperity of company owners or shareholders in the company. The population of this research is 43 companies in the Food and Beverage Sub-Sector Companies listed on the Indonesia Stock Exchange in 2019-2021. By using the purposive sampling method, a sample of 18 companies was obtained. The data used in this study is secondary data obtained from the company's annual report. The research method used is Multiple Regression Analysis to see the effect of the independent variables on the dependent variable using the SPSS version 16 program. The results of the partial t test show that earnings per share (EPS) has no significant effect on firm value. Dividend policy partially has a significant effect on firm value and the results of the simultaneous F-test show that the earnings per share variable and dividend policy have a significant effect on firm value variables.